Spectrum-effect relationship between components and antitumor activity of Lonicerae Japonicae Flos based on orthogonal partial least squares regression - Tianliang Liu; Linlin Yang; Chengming Dong; Daming Qi; Baoyu Ji; Qiguo Gao (Science of Traditional Chinese Medicine)
Abstract. Lonicerae Japonicae Flos is a significant food and traditional Chinese medicine, known as plant antibiotics. It has rich chemical constituents and significant pharmacological effects. The antitumor activity of Lonicerae Japonicae Flos has been clarified, but the study on its spectrum-effect relationship has not been reported. The compounds responsible for its antitumor activity are still unknown. In this study, processed products of Lonicerae Japonicae Flos at different temperatures were taken as experimental materials, and SMMC-7721, A549, and MGC80-3 cells were tested. The orthogonal partial least squares regression method was used to analyze the common compounds in different processed products and the antitumor activity. The results show that processed products have a stronger inhibitory effect on A549 cells and MGC80-3 cells than SMMC-7721 cells. Compounds such as secologanic acid, isochlorogenic acid A, serotonin, and chlorogenic acid play an important role in their antitumor effects.